Membranes for the Removal of Endocrine Disrupting Compounds from Aqueous Environments - Khairul Anwar, Mohamad Said; Sari, Clara; Md Rezaur, Rahman (Royal Society of Chemistry, 2024)
The advancement of membranes especially equipped with membrane technology, photocatalysis and adsorptive material has attracted much attention from researchers. Several notable features which include chemical-resistant, recyclability, unique pore structure, excellent removal capabilities with a tunable band gap for photocatalysis, and high thermal, chemical, and mechanical characteristics, have offered new insight compared to traditional membranes. Endocrine-disrupting compounds (EDC) are categorized as emerging contaminants of concern that are capable of disrupting the endocrine hormone system at micro to nano concentrations. EDC can be found ubiquitously either in an industrial area or in domestic discharge, especially in wastewater treatment plants. Conventional water treatment systems that consist of primary and secondary treatment are not designed to remove EDC due to the persistence of these compounds. Hence, studies have shown that membrane technology, advanced oxidative processes (AOP), and adsorption are promising approaches to tackle EDC. Therefore, the incorporation of AOP materials and adsorbents in the membrane could improve its abilities to remove EDC. The introduction of particles in the membrane can be materialized by physical or chemical adsorption, encapsulation, interfacial polymerization, layer-by-layer assembly, and microencapsulation.